Glucocorticoid use and factors associated with variability in this use in the Systemic Lupus International Collaborating Clinics Inception Cohort. (18th January 2018) - Little, Jayne; Parker, Ben; Lunt, Mark; Hanly, John G; Urowitz, Murray B; Clarke, Ann E; Romero-Diaz, Juanita; Gordon, Caroline; Bae, Sang-Cheol; Bernatsky, Sasha; Wallace, Daniel J; Merrill, Joan T; et al.
Abstract: Objectives: To describe glucocorticoid (GC) use in the SLICC inception cohort and to explore factors associated with GC use. In particular we aimed to assess temporal trends in GC use and to what extent physician-related factors may influence use. Methods: Patients were recruited within 15 months of diagnosis of SLE from 33 centres between 1999 and 2011 and continue to be reviewed annually. Descriptive statistics were used to detail oral and parenteral GC use. Cross sectional and longitudinal analyses were performed to explore factors associated with GC use at enrolment and over time. Results: We studied 1700 patients with a mean (s .d .) follow-up duration of 7.26 (3.82) years. Over the entire study period, 1365 (81.3%) patients received oral GCs and 447 (26.3%) received parenteral GCs at some point. GC use was strongly associated with treatment centre, age, race/ethnicity, sex, disease duration and disease activity. There was no change in the proportion of patients on GCs or the average doses of GC used over time according to year of diagnosis. Conclusion: GCs remain a cornerstone in SLE management and there have been no significant changes in their use over the past 10–15 years. While patient and disease factors contribute to the variation in GC use, between-centre differences suggest that physician-related factors also contribute. Evidence-based treatment algorithms are needed to inform a more standardized approach to GC use in SLE.